2015
DOI: 10.1186/s12898-015-0052-x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic censusing identifies an unexpectedly sizeable population of an endangered large mammal in a fragmented forest landscape

Abstract: BackgroundAs habitat degradation and fragmentation continue to impact wildlife populations around the world, it is critical to understand the behavioral flexibility of species in these environments. In Uganda, the mostly unprotected forest fragment landscape between the Budongo and Bugoma Forests is a potential corridor for chimpanzees, yet little is known about the status of chimpanzee populations in these fragments.ResultsFrom 2011 through 2013, we noninvasively collected 865 chimpanzee fecal samples across … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 98 publications
(140 reference statements)
2
51
0
Order By: Relevance
“…Importantly, TIRM and TIRMpart performed well according to these 3 criteria in both the 3‐month and 3‐year sampling periods. This is encouraging considering that previous research has emphasized TIRM when using multiple genetic CR approaches to estimate population size (Puechmaille and Petit ; Arandjelovic et al , ; McCarthy et al ). Also encouraging was the result that, in contrast to the general pattern for the models overall, TIRM and TIRMpart had higher overall performance in the 3‐year versus the 3‐month sampling period, with notably narrower confidence intervals in the former.…”
Section: Discussionsupporting
confidence: 52%
“…Importantly, TIRM and TIRMpart performed well according to these 3 criteria in both the 3‐month and 3‐year sampling periods. This is encouraging considering that previous research has emphasized TIRM when using multiple genetic CR approaches to estimate population size (Puechmaille and Petit ; Arandjelovic et al , ; McCarthy et al ). Also encouraging was the result that, in contrast to the general pattern for the models overall, TIRM and TIRMpart had higher overall performance in the 3‐year versus the 3‐month sampling period, with notably narrower confidence intervals in the former.…”
Section: Discussionsupporting
confidence: 52%
“…While chimpanzees in other ecotone regions were found to occasionally nest in woodland savanna (Baldwin et al, 1982;Hicks et al, 2014;McCarthy et al, 2015;Moore and Vigilant, 2013;Ogawa et al, 2007;Pruetz et al, 2008), all 406 chimpanzee nests found in this study were located in CCF, as was also reported for the ecotone of Republic of Côte d'Ivoire (Marchesi et al, 1995). In the CNR, chimpanzees further favor extensive CCF habitat also around their nest sites.…”
Section: Habitat Preferencessupporting
confidence: 75%
“…1) that were typed at overlapping sets of microsatellite markers. We first combined our data with that of three populations of Central chimpanzees from Loango in Gabon (Arandjelovic et al, 2011), Lobéké in Cameroon and Nouabalé-Ndoki in the Republic of Congo (Fünfstück et al, 2015) and one population of Eastern chimpanzees from Budongo-Bugoma in Uganda (McCarthy et al, 2015) and used the eight microsatellite loci D10s676, D5s1470-PIG, D4s1627, D7s817-F2, D11s2002-R2, D3s3038, D3s2459 and D7s2204 that were typed in all populations. In a second set of analyses we added two additional populations of Eastern chimpanzees from Ugalla in Tanzania (Moore and Vigilant, 2013) and Gishwati in Rwanda (Chancellor et al, 2012).…”
Section: Inferring Population Structurementioning
confidence: 99%
See 1 more Smart Citation
“…For example, genotypes can be extracted from dung and hair surveys that, via sample association patterns, can provide data on group structure and composition [4, 5]. Specific to great apes, sleeping nest sites provide information on the size of a group, whilst their spatial distribution and clustering can be used to infer territories [6].…”
Section: Introductionmentioning
confidence: 99%